Analisis Yuridis Terhadap Kasus Pencucian Uang (Money Laundering): Perspektif Hukum Perbankan Indonesia - Fenty Nur Hidayah; Marchanida Firly Nabila; Magdalena Triyas Maharani; Anggra Prayundhika Herani (JOURNAL SAINS STUDENT RESEARCH, 2025)
Money laundering is a financial crime that has a major impact on economic stability and the integrity of the banking system. This crime involves disguising the origin of illegal funds through various financial mechanisms to appear legitimate. Banking is often the main medium in the money laundering process, either through storing, transferring or disguising illegal funds. This study aims to analyze money laundering mechanisms, banking institutions in preventing this crime, as well as the implementation of regulations in Indonesia, especially based on Law no. 8 of 2010 concerning Prevention and Eradication of Money Laundering. Indonesia has also strengthened its supervision through institutions such as the Financial Transaction Reports and Analysis Center (PPATK) and the Financial Services Authority (OJK). However, cases such as the use of bank accounts to disguise funds resulting from corruption or narcotics trafficking show that regulation and supervision still face major challenges. Therefore, this research focuses on the role of banking law in preventing and eradicating money laundering in Indonesia.